2014
DOI: 10.1371/journal.pone.0090958
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of OLC1 Promotes Tumorigenesis of Human Esophageal Squamous Cell Carcinoma

Abstract: PurposeOLC1 was recently identified to be a potential oncogene. However, the role of OLC1 in human esophageal cell carcinoma (ESCC) is unknown. The aim of this study was therefore to evaluate the expression of OLC1 in human ESCC from normal, premalignant, and malignant lesions, and to clarify the mechanisms by which OLC1 contributes to the progression of ESCC. Experimental DesignTwo hundred and fourteen paired ESCC specimens, and an independent set from 28 ESCC patients, were used to analyze the correlation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Esophageal cancer is difficult to diagnose, and frequently has a poor prognosis. Therefore, it is of importance to identify new candidate markers to facilitate the early diagnosis and treatment of EC (27). KLK10 codes a secreted serine protease, whose physiological function remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal cancer is difficult to diagnose, and frequently has a poor prognosis. Therefore, it is of importance to identify new candidate markers to facilitate the early diagnosis and treatment of EC (27). KLK10 codes a secreted serine protease, whose physiological function remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Since pro-tumorigenic Rab11a-exosomes are secreted under nutrient stress conditions in cancer cell lines (Fan et al, 2019) , our data could be relevant to the study of tumour adaptation mechanisms. Some accessory ESCRT-IIIs have already been associated with human cancer: Ist1 overexpression (OLC1 in human also known as KIAA0174) has been observed in lung, breast and colorectal cancer as well as oesophageal squamous cell carcinoma (Yuan et al, 2008;Ou-Yang et al, 2014;Liu et al, 2014;Li et al, 2014) , and Chmp1A levels are reported to be increased in renal cell and pancreatic carcinomas (Li et al, 2008;Mochida et al, 2012, p. 1). It may be possible to selectively inhibit Rab11a-exosome biogenesis by interfering with accessory ESCRT-III function and therefore block adaptive responses without preventing the ubiquitin-mediated degradation of growth factor receptors in cancer cells.…”
Section: )mentioning
confidence: 99%
“…Previous studies have demonstrated that OLC1 is an oncogenic protein, as the induced overexpression of OLC1 results in anchorage-independent growth in vitro and malignant transformation in vivo . Additionally, OLC1 has been identified as overexpressed in multiple types of malignant tumor, including in lung cancer and esophageal squamous carcinoma (1,2). Thus, additional experiments were performed to confirm if the cells with mutated OLC1 may exhibit more malignant characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…A stable OLC1-overexpressing cell line KYSE150/GFP-OLC1 and its null control cell line KYSE150/GFP were constructed as previously described (2). H1299 human lung carcinoma cells were purchased from the American Type Culture Collection (Manassas, VA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation